EFFECTS OF POZZOLANAS AND FIBERS ON MECHANICAL PROPERTIES OF MORTARS IN HISTORICAL BlUILDINGS - Akbulut, Dilek Eksi; Akoz, Fevziye (DOLNOSLASKIE WYDAWNICTWO EDUKACYJNE-DWE, 2012)
In our country there are many historic buildings built in different type of construction systems like masonry, timber frame and composite structures. The conservation, restoration and strengthening studies of these historical buildings are very important as the conservation of cultural heritage. In the determination studies it is proved that in the historical masonry buildings lime mortars are used and also puzzolanic materials like brick powder, casein (milk), egg white, linseed oil, fresh blood, wax, keratin, animal fat are mixed so as to increase the durability and strengthening of the mortar. In this study, broken brick (max. 8 mm) is used as an aggregate, lime as a binding material, silica fume, fly ash, blast furnace, brick powder as puzzolanas and polymer fibre is used. According to the TS EN 196-1 standard, in 10 groups 126 pieces of 40 x 40 x 160 mm dimensioned samples are produced with four different puzzolans. Determination of the mechanical properties of mortars produced with fibers or without fibers one group of samples kept for one year in the laboratory conditions and the other group of samples is left in the atmosphere for the investigation of the durability of the effects of the atmospheric conditions. The effects of laboratory and atmospheric conditions to the mechanical properties of mortar samples are investigated with control experiments.
Keywords: Historical buildings; Lime mortars; Puzzolanas; Silica fume; Fly ash; Blast furnace slag; Brick powder; Polymer fibers; Construction & Building Technology; Engineering